2016
DOI: 10.1136/archdischild-2016-311535.61
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Use in Severe Neonatal Autosomal Dominant Polycystic Kidney Disease (Adpkd): The Pharmaceutical Challenge

Abstract: BackgroundUnlicensed medications are used all the time in the management of diseases in childhood. Tolvaptan (Jinarc®) is a vasopressin V2-receptor antagonist licensed for use to slow the progression of cyst development and renal insufficiency of ADPKD in adults with CKD stage 1 to 3 with evidence of rapidly progressing disease. Studies of animal models implicate the antidiuretic hormone arginine vasopressin and its messenger cyclic adenosine monophosphate (cAMP) as promoters of kidney-cyst cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A recent case report in Pediatric Nephrology straddles the indications for the two brands and raises some interesting questions: Gilbert et al report a case of an infant with biallelic PKD1 variants who was treated with tolvaptan [6,7]. In rare instances, like the reported case, the combination of a disease-causing ADPKD mutation on one allele with a hypomorphic variant on the other allele can cause a form of severe neonatal PKD that is mimicking the autosomal recessive form (ARPKD) [8].…”
Section: Aquaretics In the Treatment Of Hyponatremia As A Complicatiomentioning
confidence: 90%
“…A recent case report in Pediatric Nephrology straddles the indications for the two brands and raises some interesting questions: Gilbert et al report a case of an infant with biallelic PKD1 variants who was treated with tolvaptan [6,7]. In rare instances, like the reported case, the combination of a disease-causing ADPKD mutation on one allele with a hypomorphic variant on the other allele can cause a form of severe neonatal PKD that is mimicking the autosomal recessive form (ARPKD) [8].…”
Section: Aquaretics In the Treatment Of Hyponatremia As A Complicatiomentioning
confidence: 90%
“…Patients who can´t reach this threshold and whose PROPKD score is >6 should be considered for long-term tolvaptan therapy. In general, the more severe the polycystic kidney disease is the earlier tolvaptan should be administered, which has already been used successfully (offlabel) in a new-born infant with severe polycystic kidney disease ADPKD [19].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the usefulness of tolvaptan for treating severe neonatal PKD. The second case of tolvaptan use is in a neonate with severe ADPKD in the UK; tolvaptan administration relieved edema, but the kidneys remained enlarged [31]. Tolvaptan has also been used to successfully treat pediatric syndrome of inappropriate antidiuretic hormone as well as severe hyponatremia in pediatric nephrotic syndrome [32][33][34].…”
Section: Trials and Case Studies On Pediatric Adpkdmentioning
confidence: 99%
“…Polyuria was found in a female infant treated for severe ADPKD, and there have been no incidents of hypernatremia or hepatotoxicity [30]. While tolvaptan produced the expected aquaresis and blood pressure reduction in another severe neonatal ADPKD case, no AEs were reported [31]. Kerling et al [42] reported 1 case of hypernatremia which was reversible after 1 day in a study of tolvaptan for the treatment of neonates and infants with capillary leak syndrome after cardiac surgery.…”
Section: Remaining Problemsmentioning
confidence: 99%